In Vitro Management Of Fusarium Udum Causing Wilt Of Pigeonpea (Journal of Plant Disease Sciences, 2021)
Fusarium udum-caused Pigeonpea wilt is one of the most common diseases, causing significant yield losses. Fungicides, botanicals, and bio-agents were tested for their ability to inhibit Fusarium udum in vitro. Carboxin+ Thiram (0.3%), Carbendazim (0.2%), Carbendazim + Mancozeb (0.25%), Copper oxychloride (0.25%), Propiconazole (0.10%) and Thiophanate methyl (0.10%) inhibited Fusarium udum mycelial growth completely (100%). In respect of plant extract, Azadirachta indica extract inhibited Fusarium udum growth the most (71.11%), followed by Eucalyptus globules (55.55%). Among different bioagents evaluated, highest growth inhibition was achieved in Trichoderma asperellum (85.93%) followed by Trichoderma harzianum, Saccharomyces cerevisiae and Pseudomonas fluorescens.
Keywords: Bio-agents; Botanicals; Chemicals; Fusarium udum and Pigeonpea